Epigenetics: Linking Nutrition to Molecular Mechanisms in Aging - Park, Joo Hyun; Yoo, Yeongran; Park, Yoon Jung (Preventive nutrition and food science, 2017)
Healthy aging has become a major goal of public health. Many studies have provided evidence and theories to explain molecular mechanisms of the aging process. Recent studies suggest that epigenetic mechanisms are responsible for life span and the progression of aging. Epigenetics is a fascinating field of molecular biology, which studies heritable modifications of DNA and histones that regulate gene expression without altering the DNA sequence. DNA methylation is a major epigenetic mark that shows progressive changes during aging. Recent studies have investigated aging-related DNA methylation as a biomarker that predicts cellular age. Interestingly, growing evidence proposes that nutrients play a crucial role in the regulation of epigenetic modifiers. Because various nutrients and their metabolites function as substrates or cofactors for epigenetic modifiers, nutrition can modulate or reverse epigenetic marks in the genome as well as expression patterns. Here, we will review the results on aging-associated epigenetic modifications and the possible mechanisms by which nutrition, including nutrient availability and bioactive compounds, regulate epigenetic changes and affect aging physiology.